The Adjustment/Satisfaction Test (A/ST) for the Evaluation of Personalization in Broadcast Services and its Application to Dialogue Enhancement - Torcoli, Matteo; Herre, Jürgen; Fuchs, Harald; Paulus, Jouni; Uhle, Christian (IEEE Transactions on Broadcasting, 2018)
Media consumption in broadcasting is heading towards high degrees of content personalization also in audio thanks to next-generation audio systems. It is thus crucial to assess the benefit of personalized media delivery. To this end, the adjustment/satisfaction test was recently proposed. This is a perceptual test where subjects interact with a user-adjustable system and their adjustments and the resulting satisfaction levels are studied. Two configurations of this test paradigm are implemented and compared for the evaluation of Dialogue Enhancement (DE). This is an advanced broadcast service which enables the personalization of the relative level of the dialog and the background sounds. The test configuration closer to the final application is found to provide less noisy data and to be more conclusive about the quality of experience. For this configuration, DE is tested both in the case in which the original audio objects are readily available and in the case in which they are estimated by blind source separation. The results show that personalization is extensively used, resulting in increased user satisfaction, in both cases.
herre_books_journals
Keywords: Adjustment/satisfaction test (A/ST); advanced broadcast services; audio systems; blind source separation (BSS); Dialogue Enhancement (DE); digital audio broadcasting; MPEG-H; next-generation audio (NGA); perceptual evaluation; personalization; quality of experience (QoE); user satisfaction